Labor stimulation with oxytocin: effects on obstetrical and neonatal outcomes - Pedro Hidalgo-Lopezosa; María Hidalgo-Maestre; María Aurora Rodríguez-Borrego
Abstract Objective: to evaluate the effects of labor stimulation with oxytocin on maternal and neonatal outcomes. Method: descriptive and analytical study with 338 women who gave birth at a tertiary hospital. Obstetric and neonatal variables were measured and compared in women submitted and non-submitted to stimulation with oxytocin. Statistics were performed using Chi-square test, Fisher exact test, Student t-test; and crude Odds Ratio with 95% confidence interval were calculated. A p < 0.05 was considered statistically significant. Results: stimulation with oxytocin increases the rates of cesarean sections, epidural anesthesia and intrapartum maternal fever in primiparous and multiparous women. It has also been associated with low pH values of umbilical cord blood and with a shorter duration of the first stage of labor in primiparous women. However, it did not affect the rates of 3rd and 4th degree perineal lacerations, episiotomies, advanced neonatal resuscitation, 5-minute Apgar scores and meconium. Conclusion: stimulation with oxytocin should not be used systematically, but only in specific cases. These findings provide further evidence to health professionals and midwives on the use of oxytocin during labor. Under normal conditions, women should be informed of the possible effects of labor stimulation with oxytocin.